2017
DOI: 10.3906/vet-1605-17
|View full text |Cite
|
Sign up to set email alerts
|

Pathological studies and detection of different bovine papilloma virus types in buffalo cutaneous warts

Abstract: Bovine papillomatosis (BP) is distributed worldwide among cattle but is relatively less common in buffaloes. Prevalence of this disease is established in buffaloes from India (1,2) and Italy (3) caused by bovine papilloma virus (BPV). BPV is a nonenveloped double stranded DNA virus with icosahedral symmetry that infects the cutaneous and mucosal epithelia inducing hyperplastic lesions. Viral capsid proteins production takes place only in productive infections. The virion particles assemble in the granular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…It revealed that out of total 10 cutaneous wart tissue samples, only six cattle were positive for BPV-1 while all the samples were found negative for BPV-2 (Fig 1). Similar finding was observed by Jangir et al (2013), Kumar et al (2013) where they reported overall, 68.75% (11/16) and 56.25% (9/16) positivity for BPV-1 and BPV-2, respectively. BPV-1 and BPV-2 in the cutaneous warts of cattle (Pangty et al 2010;Kumar et al, 2013a andKumar et al, 2013b), buffalo (Singh and Somvanshi 2010;Kumar et al, 2013a) and yak (Bam et al, 2012).…”
Section: Resultssupporting
confidence: 86%
“…It revealed that out of total 10 cutaneous wart tissue samples, only six cattle were positive for BPV-1 while all the samples were found negative for BPV-2 (Fig 1). Similar finding was observed by Jangir et al (2013), Kumar et al (2013) where they reported overall, 68.75% (11/16) and 56.25% (9/16) positivity for BPV-1 and BPV-2, respectively. BPV-1 and BPV-2 in the cutaneous warts of cattle (Pangty et al 2010;Kumar et al, 2013a andKumar et al, 2013b), buffalo (Singh and Somvanshi 2010;Kumar et al, 2013a) and yak (Bam et al, 2012).…”
Section: Resultssupporting
confidence: 86%
“…Histopathological analysis, papilloma (exophytic), there was moderate to severe hyperkeratosis, squamous epithelial cell proliferation such as finger-like shape in the fibrovascular area, as well as hypergranulosis in the granulosum stratum similar to the report Ayman and Das [17] and Al-Salihi et al [13]. Microscopically, exophytic type fibropapilloma is the most common type and also endophytic type fibropapilloma which can lead to malignant fibrosarcoma [18].…”
Section: Discussionsupporting
confidence: 69%
“…Concerning the obtained results, it was noticed that all of the infected cases were cattle while there were no clinical cases of buffaloes and this agrees with that recorded by Jangir et al . [ 25 ] and Somvanshi [ 26 ]. Although there are many successive trials of identification and characterization of some BPVs in buffalos [ 27 , 28 ], especially that cross-species infection was recorded in cases within mixed herd systems [ 29 ].…”
Section: Discussionmentioning
confidence: 99%